PENGARUH SISTEM INFORMASI BERBASIS KOMPUTER DAN KEPERCAYAAN TERHADAP KINERJA INDIVIDUAL (STUDI EMPIRIS PERBANKAN DI KOTA MEDAN) - Henny Zurika Lubis (Jurnal Riset Akuntansi dan Bisnis, 2013)
This study is an empirical study conducted with the aim to test hypothesesabout the impact of computer-based information systems and reliance on individual performance. The data in this study were drawn from the banking company in the city of Medan. The data was collected by distributing questionnaires to the respondents 30 pieces. By using simple regression analysis, testing hypothesis 1 was done and based on a hypothesis test results are received, that the computer-based information systems have a significant influence on individual performance. The next two hypotheses are tested using the same simple regression analysis showed that the trust has a significant influence on individual performance, so that hypothesis 2 is received. For the third hypothesis using multiple regression analysis were tested simultaneously showed that computer-based information systems and trust together have a significant influence on individual performance, the hypothesis 3 accepted.